Use Of Augmented Reality As A Learning Media In Early Childhood Education Solideo Perumnas I Jayapura - Remuz Kmurawak; Diana Setyaningsih (Early Childhood Research Journal (ECRJ), 2020)
Learning media for young children is a tool used to introduce the theme as teaching materials or what is often called the curriculum for early childhood. The more sense tools are involved in the learning process, the more likely the child understands the information presented by the teacher. Recently, learning media still uses face to face methods or books. Meanwhile, early childhood is easily bored and more interested in new things. This research aims to develop a Learning media that used to introduce animals using Augmented Reality (AR) so that children can know the environment and food needed by the introduced animal. 83% of teachers and 91% of students enjoy using the application in animal recognition. KEYWORDS    Learning Media, Animal Recognition, Augmented Reality, Mobile Phone